Empowering Indonesian Coffee: A Transnational Community-Based Branding Model for Sustainable Livelihoods in the Global South - Safaruddin Husada; Ulani Yunus; Nadine Yasminah (Ilomata International Journal of Social Science, 2026)
Introduction: Indonesian specialty coffee holds strong production capacity and geographical indication (GI) potential, yet remains underrepresented in global consumer markets. This condition reflects a structural gap in agrifood value chains, where smallholder farmers are positioned primarily as raw material suppliers rather than participants in downstream branding and value creation. This study examines how community-based branding can function as an upstream capacity-building approach to address this imbalance. The research investigates the question: How can participatory branding interventions enhance branding capacity among smallholder coffee farmers prior to market activation? Novelty: This paper introduces community-based branding as an intermediate capacity-building mechanism in agrifood contexts, rather than as a market-ready branding strategy. Unlike existing studies that focus on certification, price premiums, or downstream branding actors, this research integrates participatory action research with branding and GI discourse to foreground farmers’ branding literacy, narrative ownership, and collective agency—an area that remains insufficiently explored in current literature. Methods: The study employs a participatory action research (PAR) design involving smallholder coffee farming communities in Indonesia. Data were collected through pre- and post-intervention assessments, participatory observation, and facilitated branding workshops. An exploratory consumer awareness survey conducted in Sydney, Australia (n = 57) was used to provide contextual insight into downstream brand awareness. Results: The findings indicate observable improvements in farmers’ understanding of branding concepts, geographical indication, and collective brand ownership. The exploratory survey reveals limited consumer awareness of Indonesian coffee brands, underscoring the relevance of upstream branding capacity development. Conclusion: The study concludes that community-based branding can support early-stage branding capacity development among smallholder farmers, serving as a foundation for more equitable participation in branding processes. The main implication is that branding initiatives in agrifood systems should prioritize community-level capacity building alongside regulatory and market-oriented strategies.